Evidence of ocean warming in Uruguay’s fisheries landings: The mean temperature of the catch approach - Gianelli, Ignacio (2019)
Distribution, abundance and life history traits of marine fish and invertebrates are increasingly affected by ocean warming. Consequently, landings of traditional fisheries and their relative species composition could potentially be modified. The mean temperature of the catch (MTC) concept, which refers to the average inferred temperature preference of exploited species weighted by their annual catch for a given area, was applied to Uruguay’s industrial fisheries. This approach allowed us to assess the evidence of ocean warming in long-term Uruguayan landings (1973−2017), which were mostly obtained from a major marine warming hotspot. Results showed a marked shift in MTC through time, with the first 10−15 yr characterized by a decreasing trend, but subsequently increasing steadily over time. Long-term effects of ocean warming have led to a shift from cool-water to warm-water species in the relative representation of local landings. A significant and consistent association between sea surface temperature and MTC increase was observed, even when accounting for other drivers. This study provides the first quantitative evidence that ocean warming has been increasingly affecting Uruguayan industrial fisheries during the past decades, and calls for an urgent need to consider environmental changes to properly manage fish stocks, particularly those shared with neighboring countries.